PEMANFAATAN MEDIA AUDIO VISUAL DALAM KETERRAMPILAN BERBICARA PADA SISWA FASE D DI SMP NEGERI 24 KOTA JAMBI - Karina Pradipta Sukandi; Agus Setyonegoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the use of audio-visual media on the speaking skills of eighth grade students (phase D) at SMP Negeri 24 Kota Jambi. The background of this study is based on the low speaking skills of students caused by a lack of variety in learning methods and minimal use of technology-based learning media. This study used a quantitative approach with a Pre-Experimental Design (One Group Pretest-Posttest Design) method. The research sample consisted of 32 eighth-grade students from SMP Negeri 24 Kota Jambi, selected using purposive sampling. Data collection techniques were conducted through interviews, observations, tests, and documentation. The data were analyzed using normality tests, homogeneity tests, t-tests, and N-Gain tests with the help of the SPSS version 31 program. The results showed that the average pretest score was 13.22 and the average posttest score was 22.22. Based on the t-test results, a significance value of 0.001 < 0.05 was obtained, which means that there was a significant difference between the pretest and posttest results. In addition, the N-Gain test results showed an increase in the moderate category, with an average score of 6.2. Thus, it can be concluded that the use of audio-visual media has a significant effect on improving students' speaking skills. This study implies that Indonesian language teachers can utilize audio-visual media as an effective learning tool.